Pengaruh Progressive Muscle Relaxation terhadap Stres dan Penurunan Kadar Gula Darah pada Pasien Diabetes Melitus Tipe 2 - Ungkas Herlambang; Kusnanto Kusnanto; Laily Hidayati; Hidayat Arifin; Rifky Octavia Pradipta (Universitas Airlangga, 2019)
Introduction: Diabetes Mellitus is a disease that occurs because the body is unable to produce insulin or the body cannot use insulin effectively. The purpose of this study was to find out the effect of Progressive Muscle Relaxation (PMR) on stress and blood glucose decrease in patients who have diabetes mellitus type 2 disease.Method: The design of this study is quasi-experimental study. The population of this study were the patients who have type 2 of diabetes mellitus disease at Puskesmas Kedungdoro and Puskesmas Medokan Ayu. There would be 70 respondents chosen based on inclusion and exclusion criteria. The researcher chose the purpose sampling technique in choosing the participants in this research. The independent variable in this study was Progressive Muscle Relaxation (PMR). The dependent variable in this study were stress and blood glucose decrease. The data in this study were collected using questionnaires and measurement of pre-prandial blood glucose level. Data were analyzed using analysis of Wilcoxon and paired t-test for pre-post measurements, then for the inter groups the researcher used Mann-Whitney analysis.Results: The results showed that there was an effect of PMR on stress (p = 0.001) and in decreasing blood glucose (p = 0.021).Discussion: PMR is a relaxation focused on the patient’s attention in distinguishing the group of muscle when they relaxed than while in contraction condition. Thus, the patients are expected to be able to manage the body condition in managing stress and blood sugar decrease. For health officers, they are expected to use the PMR as the combination in reducing stress and blood glucose to improve the quality of life of the patients who have diabetes type 2 disease.